The Legal Construction of Business Ethics to Prevent Abuse in Pre-Contractual Bank Credit - Afina Khoirunnisa; Turisno, Bambang Eko (Jurnal Cakrawala Hukum, 2026)
Bank credit distribution plays a strategic role in supporting economic growth, but it also carries the potential for abuse of authority, particularly at the pre-contractual stage. This stage affords bank officials broad professional discretion, thereby creating opportunities for misconduct that formal legal mechanisms cannot always address. This situation indicates that problems relate not only to institutional aspects but also to the quality of the use of authority by individuals. This study aims to analyze the role of business ethics and formulate an ethical construct as a preventive mechanism. The method used is normative legal research through a literature review. The results of the study indicate that control cannot simply rely on formal procedures but requires ethics as a standard in decision-making. The study produces a three-tiered legal construct comprising: (1) mandatory conflict-of-interest disclosure before credit recommendation, (2) ethical review as a supplementary layer in credit approval, and (3) integration of ethical documentation requirements into credit SOPs. These mechanisms operationalize business ethics as a preventive instrument within the pre-contractual legal gap.